Analisis Strategi Pelaku Usaha Menghadapi Persaingan Pasar Lokal Melalui Pemasaran Online dan Offline: Model Lima Kekuatan Porter di Dealer Agung Motor Honda Cianjur - Rahayu, Nanda Sri; Wibowo, Indrajati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the strategies used by business actors in facing local market competition through Porter's Five Forces Model approach, which includes: the threat of new entrants, the threat of substitute products, the bargaining power of suppliers, the bargaining power of consumers, and the intensity of competition between competitors. This research uses a qualitative method with a descriptive approach. Data collection techniques were conducted through in-depth interviews with three categories of informants, namely business owners, employees, and consumers. Data analysis was conducted by identifying patterns, differences, and linkages between the strategies applied and aspects of Porter's Five Forces Model. The results showed that the main strendgth in local competition lies in the high intensity of competitors and the increasing number of alternative products offered. The integration strategy between online and offline marketing is proven to help dealers reach consumers more widely and build customer loyalty. The use of social media, digital promotions, and direct-to-consumer services such as exhibitions and local community partnerships are key to adaptation in the digital era. By understanding Porter's five aspects in depth, businesses can formulate strategies that are more adaptive, innovative, and highly competitive in the local market.